2000
DOI: 10.1042/cs0990269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of balloon mitral valvuloplasty on systemic and regional left atrial levels of prothrombin fragment 1+2 in mitral stenosis

Abstract: A proportion of mitral stenosis patients with left atrial spontaneous echo contrast but without thrombus exhibit a regional hypercoagulable state, characterized by increased left atrial levels, but normal venous levels, of prothrombin fragment 1+2 (F1+2), a marker of thrombin generation. Valve dilatation by balloon mitral valvuloplasty has beneficial effects on left atrial spontaneous echo contrast, but its effect on left atrial thrombin generation is unknown. We examined the effects of balloon mitral valvulop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Contrary to the assertion of Li-Saw-Hee and Lip that thrombogenesis in cardiac disease is likely to be a generalized process, we believe that there is now abundant evidence from our group [1][2][3][4] and others [5][6][7] which supports the existence of a localized increase in left atrial coagulation activity in mitral stenosis. Moreover, this coagulation activation is not primarily due to atrial fibrillation as it is also observed in patients with sinus rhythm who have left atrial spontaneous echo contrast [1,7].…”
Section: Foo Leong Li-saw-hee and Gregory Y H Lipcontrasting
confidence: 97%
See 3 more Smart Citations
“…Contrary to the assertion of Li-Saw-Hee and Lip that thrombogenesis in cardiac disease is likely to be a generalized process, we believe that there is now abundant evidence from our group [1][2][3][4] and others [5][6][7] which supports the existence of a localized increase in left atrial coagulation activity in mitral stenosis. Moreover, this coagulation activation is not primarily due to atrial fibrillation as it is also observed in patients with sinus rhythm who have left atrial spontaneous echo contrast [1,7].…”
Section: Foo Leong Li-saw-hee and Gregory Y H Lipcontrasting
confidence: 97%
“…While this does not completely exclude a residual effect of warfarin in our study, our previous finding of no difference in venous or left atrial F1j2 levels between patients who had or had not been on warfarin prior to the valvuloplasty procedure [1], suggests that any such effect was likely to have been small. Furthermore, any minor suppression of coagulation activity by warfarin would have been present at the beginning of the procedure and does not explain the changes in F1j2 levels occurring after balloon mitral valvuloplasty [4].…”
Section: Foo Leong Li-saw-hee and Gregory Y H Lipmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that relieving the obstruction across the MV by valvuloplasty decreases the left atrial afterload, leading to improvements in LA/LAA contractility, 34,35 decrease in stasis 36,37 and decrease in the level of procoagulants. 38,39…”
Section: Discussionmentioning
confidence: 99%